ZnO-CuxO heterostructure photocatalyst for efficient dye degradation. (August 2020) - Nandi, Prami; Das, Debajyoti
Abstract: A simple aqueous solution process was used for the synthesis of Cu-loaded ZnO nanorod structures in which highly crystalline and hexagonal wurtzite ZnO, cubic CuO and Cu2 O phases coexist. Absorption/emission characteristics identify band gap narrowing, which facilitates visible light absorption, as a consequence of hybridization of O 2p bands with Cu 3 d bands of the ZnO-Cu x O heterostructure system. With use of the specific band energy position of the individual components (i.e., ZnO, Cu2 O, and CuO), photogenerated electrons and holes could be made to migrate separately and thereby the carrier recombination could be delayed, making them amply available for photocatalytic reactions. The available electrons plausibly produce superoxide radical anion (O2 · − ), while holes generate hydroxyl radicals (· OH), which are reactive agents for dye degradation. Furthermore, the formation of a depletion region via Cu-induced charge separation within the ZnO-Cu x O heterostructure and thermal-energy-mediated abstraction of the electric field barriers and subsequent migration of the positively charged defects from the subsurface region toward the interface lead to efficient photocatalytic performance. Graphical abstract: Image 1 Highlights: Crystalline hexagonal wurtzite ZnO, cubic CuO and Cu2 O phases coexist in Cu-loaded ZnO nanorods grown by simple aqueous solution process. Band gap narrowing via hybridization of O 2p with Cu 3d bands in ZnO-Cu x O promotes visible light absorption. Specific band positions of ZnO, Cu2 O, and CuO help migration of charges and impede carrier recombination. Available electrons and holes produce O2 − and OH radicals for dye degradation. Optimized Cu loading results in superior photocatalytic activity in ZnO-Cu x O heterostructure nanocomposites.